2020
DOI: 10.1186/s43055-020-00247-6
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of 3D-FLAIR magnetic resonance sequence in detection of white matter brain lesions in multiple sclerosis

Abstract: Background MS is common demyelinating disease in which standard T2 and 2D-FLAIR MRI sequences play important role in its diagnosis. Recently, 3D-FLAIR sequence is used and has a role that is evaluated compared to standard sequences. Results This study was performed on 20 selected MS patients. Brain MRI was performed using routinely used T2 and 2D FLAIR sequences, and 3D-FLAIR sequence was added. 3D-FLAIR images were reformatted, and all images were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…3D FLAIR sequence showed significantly more lesions than 2D FLAIR, that in keeping with Gramsch et al, [13] that state that adding 3D FLAIR sequence in standard MS protocols can considerably increase MS lesion detection and provide the possibility of an adequate replacement of both axial 2D FLAIR and mid-sagittal T2W sequences. This results also matched with Tawfik et al, [14] and Patzig et al, [12] who used 3 Tesla MRI machine.…”
Section: Discussionsupporting
confidence: 89%
“…3D FLAIR sequence showed significantly more lesions than 2D FLAIR, that in keeping with Gramsch et al, [13] that state that adding 3D FLAIR sequence in standard MS protocols can considerably increase MS lesion detection and provide the possibility of an adequate replacement of both axial 2D FLAIR and mid-sagittal T2W sequences. This results also matched with Tawfik et al, [14] and Patzig et al, [12] who used 3 Tesla MRI machine.…”
Section: Discussionsupporting
confidence: 89%
“…Limitations still exist, however, as some authors have shown that T2/FLAIR WMHs overestimate neuropathologically confirmed demyelination in the periventricular areas but underestimate it in the deep WM [ 45 ], and overall sensibility and specificity hovers around 80% to 90%. As with all MRI measurements, higher field strengths and resolutions (3D versus 2D) will produce better results [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The main reason for this tendency might be that 3D images take more time to complete compared with 2D images, which may present an issue when treating a large number of patients and processing long waiting lists. However, because 3D images have a higher sensitivity for MS lesions in the periventricular region, deep white matter, juxta-cortical region, and infratentorial region [20,21], they are always recommended in MR protocol.…”
Section: Discussionmentioning
confidence: 99%